Relationship between the pressure at the casing wall and at the blade tip for a vibrating turbine blade - Alshroof, O.; Forbes, Gareth; Randall, R. (Australasian Fluid Mechanics Society, 2010)
A recent research program has identified the possibility of using the analysis of casing wall pressures in the indirect measurement of gas turbine rotor blade vibration amplitudes [1]. Analytical modelling of the casing wall pressures and reconstruction of rotor blade vibration amplitudes from the analysis of these simulated pressure signals have shown potential advantages over current non-contact rotor blade vibration measurement methods. However, the modelling made some fundamental assumptions about the casing wall pressure. One of the assumptions made was that the pressure at the blade tip is not significantly different from that measured across the clearance gap at the casing wall. This fluid-structure hypothesis is investigated in this paper. Unsteady computational fluid dynamic modelling of the flow conditions around the blade surface, combined with the blade structural motion, is performed numerically, and the distributions of the pressure across the rotor blade tip and casing clearance gap are investigated and reported.